Digital-PCR for gene expression: impact from inherent tissue RNA degradation. Issue 1 (December 2017) - Millier, Melanie; Stamp, Lisa; Hessian, Paul
Abstract Subtle molecular differences indicate the heterogeneity present in a number of disease settings. Digital-PCR (dPCR) platforms achieve the necessary levels of sensitivity and accuracy over standard quantitative RT-PCR (qPCR) that promote their use for such situations, detecting low abundance transcript and subtle changes from gene expression. An underlying requisite is good quality RNA, principally dictated by appropriate tissue handling and RNA extraction. Here we consider the application of dPCR to measures of gene expression in pathological tissues with inherent necrosis, focusing on rheumatoid subcutaneous nodules. Variable RNA fragmentation is a feature of RNA from such tissues. Increased presence of transcript fragmentation is reflected in a proportionate decrease in Agilent DV200 metric and downstream, a reduction in endogenous control genes' expression, measured by RT-dPCR. We show that normalisation of target gene expression to that for endogenous control genes sufficiently corrects for the variable level of fragmented RNA. Recovery of target gene values was achieved in samples comprising as much as 50 percent fragmented RNA, indicating the suitability and appropriate limitation of such data treatment when applied to samples obtained from inherently necrotic tissues.